Morphological and Phylogenetic Evidences Reveal Four New Species of Cantharellus Subgenus Cantharellus (Hydnaceae, Cantharellales) From China - Zhang, Yu-Zhuo; Lin, Wen-Fei; Buyck, Bart; Liang, Zhi-Qun; Su, Ming-Sheng; Chen, Zuo-Hong; Zhang, Ping; Jiang, Shuai; An, Dong-Yu; Zeng, Nian-Kai (Frontiers in Microbiology, 2022)
Species of Cantharellus subgenus Cantharellus are interesting and important for their mycorrhizal properties, medicinal values, and edibility. In China, there are many undescribed species of the subgenus. In this study, four new species of subg. Cantharellus, viz. Cantharellus albopileatus, Cantharellus chuiweifanii, Cantharellus pinetorus, and Cantharellus ravus from Hainan and Hunan Provinces, respectively, were described based on morphological and phylogenetic evidence as a contribution to the knowledge of the species diversity in China. Detailed descriptions, color photographs of fresh basidiomata, and line drawings of microstructures of these four new species are presented as well as comparisons with related species.